A New Megophrys Kuhl and Van Hasselt (Amphibia: Megophryidae) from southwestern Sumatra, Indonesia - Munir, Misbahul; Hamidy, Amir; Farajallah, Achmad; Smith, Eric N. (Zootaxa, 2018)
Megophrys lancip sp. nov., from the Bukit Barisan mountain range of southwestern Sumatra, Indonesia, is described on the basis of molecular and morphological evidence. The new species is distinguished from its congeners in Sumatra, Java, Borneo, and the Philippines by having a medium-sized body, snout with an extremely pointed rostral appendage, a medium-sized triangular eyelid appendage, a dorsolateral fold extending from just behind the eye to the groin, vomerine teeth, vocal slits, nuptial pads on the dorsomedial surface of the first and second fingers in males, and in lacking a Y, X, or H-shaped fold on the dorsum. Morphologically, the new species is most similar to M. montana, but it has a longer rostral appendage, shorter eyelid appendages, and less developed toe webbing. We also evaluate the taxonomic status of M. parallela and comment on the occurrence of M. aceras in Sumatra.